2019
DOI: 10.1186/s12889-019-7648-6
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic characteristics associated with alcohol consumption and alcohol-related consequences, a latent class analysis of The Norwegian WIRUS screening study

Abstract: Background: For alcohol, the association with socioeconomic status (SES) is different than for other public health challengesthe associations are complex, and heterogeneous between socioeconomic groups. Specifically, the relationship between alcohol consumption per se and adverse health consequences seems to vary across SES. This observation is called the 'alcohol harm paradox'. This study aims to describe different patterns of alcohol use and potential problems. Next, the associations between subgroups charac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
2
16
1
Order By: Relevance
“…Although detailed information about SES was not included in the present study, we confirmed a relationship between level of education (which are closely related to SES) and drinking behavior (Russell et al, 2016). Due to the close relationship between SES and negative consequences of alcohol use (Skogen et al, 2019), future studies should investigate the importance of SES on the relation between ADHD symptoms and problems associated with insomnia and alcohol consumption.…”
Section: Discussionsupporting
confidence: 66%
“…Although detailed information about SES was not included in the present study, we confirmed a relationship between level of education (which are closely related to SES) and drinking behavior (Russell et al, 2016). Due to the close relationship between SES and negative consequences of alcohol use (Skogen et al, 2019), future studies should investigate the importance of SES on the relation between ADHD symptoms and problems associated with insomnia and alcohol consumption.…”
Section: Discussionsupporting
confidence: 66%
“…When looking at the general population, the high alcohol use among students may also be explained by the fact that there is a peak in alcohol consumption in the age period between 18 and 29 years ( 8 , 9 ). In younger age groups, some studies have also found that high and harmful alcohol use increase more sharply with lower socioeconomic status in countries such as England ( 10 ) and Norway ( 11 ). In contrast, a study with undergraduate students from Brazil found that students with higher monthly family income reported higher alcohol use than students with lower monthly family income ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study employed the JDC and ERI questionnaires, which cover many relevant aspects of the work environment. However, as described in more detail in other publications from the WIRUS screening study [ 18 , 19 , 32 , 34 , 35 ], the employees in the study sample were, compared with the entire Norwegian workforce, older and highly educated and had female employees overrepresented. The sample was considerably more representative for Norwegian public and state sector employees, than for private sector employees.…”
Section: Discussionmentioning
confidence: 99%